Gut Dysbiosis and Intestinal Barrier Dysfunction Promotes IgA Nephropathy by Increasing the Production of Gd-IgA1 - Tang, Yuyan; Zhu, Yifan; He, Haidong; Peng, Yinshun; Hu, Ping; Wu, Jiajun; Sun, Weiqian; Liu, Ping; Xiao, Yong; Xu, Xudong; Wei, Minggang (Frontiers in Medicine, 2022)
Background Immunoglobulin A nephropathy (IgAN) is the most common type of primary glomerular disease in adults worldwide. Several studies have reported that galactose-deficient IgA1 (Gd-IgA1) is involved in the pathogenesis of IgAN. Methods Thirty-five IgAN patients diagnosed by renal biopsy for the first time served as the experimental group, who were hospitalized in our department. Twenty normal healthy cases in the physical examination center of our hospital served as the control group. Then the levels of Gd-IgA1 in serum and urine, intestinal mucosal barrier injury indexes (Diamine oxidase (DAO), serum soluble intercellular adhesion molecule-1 (sICAM-1), D-lactate (D-LAC), and Lipopolysaccharide (LPS)), and inflammatory factors (interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α)) in serum samples were detected. Fecal samples were collected to detect intestinal microbiota using 16s rDNA sequencing. Then, we assessed possible correlations among clinical and laboratory findings. Results The levels of Gd-IgA1 of IgAN both in serum and urine were higher than that of healthy control. Furthermore, urine Gd-IgA1 level was positively correlated with serum creatinine level, 24h urine protein, M, S and T in the Oxford classification. ROC curve analysis showed that urine Gd-IgA1 has a greater diagnostic value (AUC=0.9714, 95% CI, 0.932–1; P<0.0001) for IgAN. The best cutoff value for urine Gd-IgA1was 0.745ng·l/ml·μmol (sensitivity,94%; specificity, 95%). The intestinal mucosal barrier damage indexes (DAO, sICAM-1, D-LAC and LPS) were increased in IgAN patients, which were positively correlated with Gd-IgA1 levels (P < 0.05) both in serum and urine. The levels of inflammatory factors in IgAN patients were increased. 16s rDNA analysis showed that intestinal microbiota in IgAN patients was disordered compared with that of healthy subjects. Actinobacteria, Bifidobacterium, Blautia, Bifidobacteriaceae and Bifidobacteriales were decreased in IgAN, and Shigella was increased. And these decreased floras were negatively correlated with urine Gd-IgA1 significantly and the level of DAO, sICAM-1, D-LAC and LPS. Conclusions The urine Gd-IgA1 levels may be a Non-invasive biological marker for evaluating kidney injury in IgAN. Gut flora dysbiosis and intestinal barrier dysfunction may be involved in Gd-IgA1 expression.